KAPASITAS BIROKRASI DALAM ADAPTASI SISTEM DIGITAL PADA PELAYANAN KEPROTOKOLAN - Muharomdoni, Wahyu; Setyowati, Yuli (Penerbit Lafadz Jaya, 2026)
The digitalization of public administration has encouraged changes in the management of local government protocol services, yet the adaptation process often encounters structural and cultural challenges within the bureaucracy. This article aims to analyze bureaucratic capacity in adapting digital systems in local government protocol services. The study employs a qualitative approach using a literature review method by examining scientific articles, books, and policy documents relevant to digital transformation, bureaucratic capacity, and public service management. The analysis focuses on identifying key factors that influence the ability of bureaucratic institutions to respond effectively to digital change. The results indicate that bureaucratic capacity is shaped by the quality of human resources, institutional commitment, leadership orientation, organizational culture, and the availability of technological infrastructure. Limited technical competence, resistance to organizational change, weak coordination among organizational units, and insufficient capacity-building programs emerge as major constraints in the adaptation process. These conditions affect the effectiveness and consistency of digital-based protocol services. The study concludes that the success of digital adaptation in protocol services is not solely determined by technological adoption, but also by the strengthening of bureaucratic capacity through sustainable institutional development and cultural transformation. This article provides a conceptual contribution for local governments in designing strategies to enhance bureaucratic readiness in managing digital-based protocol services.